The Effectiveness of Entrepreneurship Mentoring in Developing Perfume-Making Hard Skills Among MSME Groups - Arvenia Fortuna B; Satrio Aji P; Dede Purwanti; Ladilyono Ladilyono; Achmad Agus Yasin Fadli; Mukhlis Chatio (The Future of Education Journal, 2026)
This community service activity is entitled "Effectiveness of Entrepreneurship Assistance in Forming Perfume Making Hard Skills in MSME Groups". This activity is motivated by the opportunity for a laundry perfume business as a home product that can be developed by MSME groups, PKK women, home business actors, and people who are interested in simple businesses. Implementation of activities is carried out through entrepreneurship assistance in the form of delivering materials, introduction to ingredients, perfume making practices, simulations of COGS and selling price calculations, discussions and evaluations. The material provided includes home business conditions, potential for laundry perfume businesses, HR competencies, perfume making materials, production processes, cost calculations, determining selling prices, and simple digital marketing via social media. The results of the activity showed that participants participated in the activity enthusiastically, knew the ingredients for making perfume, understood the function of the ingredients, were able to follow the perfume making process, and understood the basics of calculating COGS and selling prices. Participants also gain an understanding of the use of WhatsApp, Facebook, Instagram and TikTok as a means of product promotion. Based on the results of the activity, entrepreneurship assistance was considered effective in forming hard skills for making laundry perfume and providing initial provisions for participants to develop home business opportunities.